Pengaruh Paparan Sediaan Nanopartikel Ekstrak Etanol Daun Mimba terhadap Struktur dan Fungsi Ren Tikus Sprague Dawley Jantan - Nuraini, Ulfah (Faculty of Veterinary Medicine, Universitas Gadjah Mada bekerjasama dengan PB PDHI, 2025)
Technological advances in developing herbal plants as medicine continue to increase in Indonesia in finding herbal ingredients as medicine because they are considered safer, more practical and cheaper by the community compared to using synthetic drugs and easy to find the desired herbal ingredients. Neem plants (Azadirachta indica A.Juss) are herbal plants that have high antioxidant content and have the potential as medicine. The obstacle in oral administration is the low bioavailability of drugs and the distribution of active compounds in herbal plants. One way to overcome this problem is by packaging herbal plant extracts into smaller particle forms. This study used 32 rats aged 2 months which were divided into 4 treatments, each treatment had 8 replications, namely K-, K+, P1 and P2. The results showed that the administration of nanoparticle-chitosan preparations of ethanol extract of neem leaves 1; 0.5 and 1; 1 had no significant effect on glomerular diameter, Bowman's capsule diameter, kidney weight, creatinine levels and MDA levels p> 0.05 it can be concluded that the administration of nanoparticle-chitosan preparations of ethanol extract of neem leaves has no significant effect on the kidneys so that it can deliver the Bioactive compounds of neem leaves to the target organ, namely the kidneys and can minimize histological damage and kidney function of male white rats with the presence of antioxidant compounds in neem leaves.Technological advances in developing herbal plants as medicine continue to increase in Indonesia in finding herbal ingredients as medicine because they are considered safer, more practical and cheaper by the community compared to using synthetic drugs and easy to find the desired herbal ingredients. Neem plants (Azadirachta indica A.Juss) are herbal plants that have high antioxidant content and have the potential as medicine. The obstacle in oral administration is the low bioavailability of drugs and the distribution of active compounds in herbal plants. One way to overcome this problem is by packaging herbal plant extracts into smaller particle forms. This study used 32 rats aged 2 months which were divided into 4 treatments, each treatment had 8 replications, namely K-, K+, P1 and P2. The results showed that the administration of nanoparticle-chitosan preparations of ethanol extract of neem leaves 1; 0.5 and 1; 1 had no significant effect on glomerular diameter, Bowman's capsule diameter, kidney weight, creatinine levels and MDA levels p> 0.05 it can be concluded that the administration of nanoparticle-chitosan preparations of ethanol extract of neem leaves has no significant effect on the kidneys so that it can deliver the Bioactive compounds of neem leaves to the target organ, namely the kidneys and can minimize histological damage and kidney function of male white rats with the presence of antioxidant compounds in neem leaves.